Culture, Cognition, and Emotion in China's Religious Ethnic Minorities Voices of Suffering among the Yi - Ting, Rachel Sing-Kiat (Palgrave Studies in Indigenous Psychology, 2018)
This study examines the suffering narratives of two religious communities-Bimo and Christian-of the Yi minority who reside in the remote mountains of Sichuan and Yunnan, China, respectively. It is informed by the theoretical framework of ecological rationality, which posits that emotions influence, and are influenced, by cognitive styles that have co-evolved with the ecological niche of a culture. It was predicted and found that in times of adversity, traditional religious communities may differ in emotion expression, causal attribution, and help seeking behavior, with far-reaching ramifications in how they are uniquely vulnerable to the pitfalls of modernization. The authors hope that the voices of the study participants, heard through their harrowing narratives, may inspire a deepened sensitivity to the plight of rural Chinese communities as China races to become superpower in the global economy. .